2007
DOI: 10.1016/j.fishres.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Fishing power increases continue in Queensland's east coast trawl fishery, Australia

Abstract: The Queensland east coast trawl fishery is by far the largest prawn and scallop otter trawl fleet in Australia in terms of number of vessels, with 504 vessels licensed to fish for species including tiger prawns, endeavour prawns, red spot king prawns, eastern king prawns and saucer scallops by the end of 2004. The vessel fleet has gradually upgraded characteristics such as engine power and use of propeller nozzles, quad nets, global positioning systems (GPS) and computer mapping software. These changes, togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…see [32]). These increases are not limited to the NPF as similar efficiency increases have been observed in the adjacent Queensland east coast prawn fishery [33].…”
Section: Boat Licences Versus Minimum Quota Holdingssupporting
confidence: 76%
“…see [32]). These increases are not limited to the NPF as similar efficiency increases have been observed in the adjacent Queensland east coast prawn fishery [33].…”
Section: Boat Licences Versus Minimum Quota Holdingssupporting
confidence: 76%
“…Several studies have shown that fishing power in the QECOTF sectors has increased by 0.4-3.6% annually (O'Neill et al, 2003;O'Neill and Leigh, 2007;Braccini et al, 2012;Kienzle et al, 2014). All of these studies modelled logbook daily target species catch as a function of vessel characteristics, including vessel length, engine horse power, trawl speed, propeller size, global positioning system, net head rope length, BRDs, and other gears.…”
Section: Comparison Of Methodsmentioning
confidence: 99%
“…See, for example, Gascuel et al (1993) on fishing power in eastern Atlantic tuna fisheries; Holst et al (2002) on cod gill netters in the Baltic; Damalas et al (2014) on Greek demersal trawlers; O'Neill et al (2003) and O'Neill and Leigh (2007) on demersal trawlers off Queensland, Australia; Kimura (1981) on ocean perch trawlers in the north-east Pacific; Brown et al (1995) on the Western Australian rock lobster fishery; and Robichaud et al (1999) on coral reef fish traps in the Caribbean.…”
Section: Introductionmentioning
confidence: 99%